2014
DOI: 10.15274/nrj-2014-10033
|View full text |Cite
|
Sign up to set email alerts
|

Into the Septum I Go, a Case of Bilateral Ectopic Infraorbital Nerves: A Not-to-Miss Preoperative Sinonasal CT Variant

Abstract: An ectopic course of the infraorbital nerve is a very rare anatomical variant of the sinonasal anatomy that carries the risk of inadvertent nerve injury during functional endoscopic sinus surgery. We describe herein a case of bilateral ectopic course of the infraorbital nerve into a maxillary sinus septum detected on computed tomography in a patient complaining of chronic headache and facial pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…There is little in literature about variation related to IOC. Chandra and Kennedy [16], Elnil et al [23] and Mailleux et al [47] reported cases of IOC passing through in the maxillary sinus. Ference et al [26] reported this variation in 12.5% of 200 cases, Lantos et al [41] reported it in 10.8% of 500 cases and Yenigun et al [79] reported in 12.3% of 750 cases.…”
Section: The Angle Between the Ioc And The Axial Planementioning
confidence: 99%
See 1 more Smart Citation
“…There is little in literature about variation related to IOC. Chandra and Kennedy [16], Elnil et al [23] and Mailleux et al [47] reported cases of IOC passing through in the maxillary sinus. Ference et al [26] reported this variation in 12.5% of 200 cases, Lantos et al [41] reported it in 10.8% of 500 cases and Yenigun et al [79] reported in 12.3% of 750 cases.…”
Section: The Angle Between the Ioc And The Axial Planementioning
confidence: 99%
“…FESS procedure is based on the theory that the opening of the obstructed pathway of osteomeatal drainage complexes will restore the normal ventilation of the sinuses [38] Dry skull R 7.19 ± 1.39 L Kazkayasi et al [38] X-ray R 7.45 ± 0.95 L Hwang et al [34] HRCT R 9.4 ± 1.6 9.7 ± 1.7 9.6 ± 1.7 29.1 ± 1.8 26.9 ± 1.9 26.5 ± 1.9 L Cutright et al [21] Cadaver [20] Dry skull R 8.0 (7.0-9.0) 8.0 (7.0-9.0) L 8.0 (7.0-9.0) 8.0 (6.5-9.0) Chrcanovic et al [18] Dry L -left; R -right; F -female; M -male; CBCT -cone-beam computed tomography; CT -computed tomography; IOF-PM -the distance between IOF and the occlusal plane of the second premolar tooth; IOF-LOR -the distance between IOF and lateral orbital rim; IOF-FZS -the distance between IOF and vertical axis of lateral rim of frontozygomatic suture; ST -skin thickness over IOF (skin thickness) *Significant difference; L -left; R -right; F -female; M -male; CBCT -cone-beam computed tomography; MDCT -multidetector computed tomography; IOF-LNW -the distance between infraorbital foramen and the lateral wall of the nasal cavity; IOF-PA -the distance between infraorbital foramen and preform aperture in cases of chronic sinusitis [17]. Prior to FESS, Mailleux et al [47] and Elnil et al [23] proposed CT imaging as a preoperative procedure to reduce complications. Lantos et al [41] reported a high risk of ION injury in maxillary sinus with chronic inflammation, neoplasms, and patients with these variations in resection of an inverted papilloma require an antral punch to introduce a balloon dilation catheter to approach the maxillary infundibulum.…”
Section: The Angle Between the Ioc And The Axial Planementioning
confidence: 99%
“…If the mucosa remained in the area lateral to the infraorbital canal, the ION would be located medially to the POMC. In particular, it has been reported that in some individuals there is an ectopic ION coursing in the maxillary sinus septum, causing the infraorbital canal to float in the maxillary sinus as a normal variation of ION location [13, 16]. In such a situation, the extent of the deviation of the nerve due to the pressure of cyst formation may be larger, causing the ION to reach around the medial wall of the POMC.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The long-term consequence of injury to the ION is best described in the setting of trauma, specifically in zygomaticomaxillary complex fractures, in which injury to the ION occurred in 64.4% of cases in 1 series of 478 patients with unilateral fractures. 11 Traumatic ION injury results in ipsilateral paresthesias and numbness of the nose and lip, and we would expect similar outcomes in the setting of iatrogenic injury to a protruding ION during sinus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This may leave the ION susceptible to injury during endoscopic or open sinus surgery. To date, just 3 case reports exist in the literature describing this variant, 2,3 with no large studies describing the frequency with which it occurs. The aim of this study was to establish the prevalence of infraorbital nerve protrusion into the maxillary sinus and define its common characteristics.…”
mentioning
confidence: 99%